الأولويات البحثية لدى الجماعة الانثربولوجية المصرية - موسى بدوي, أحمد (Changement Social, 2018)
The field of anthropologydid not receivesufficient attention in Egypt. Which has negativelyaffecteditsdevelopment as an authenticknowledge system withinEgyptianacademies. This meansthatEgyptiananthropology has not developedenough to overcome the stage of imitating Western anthropologicalheritageinto interactive, constructive criticism of the Western model. Thus, the Egyptiananthropological  model has not reachedenoughmaturitythatwouldallowit to produceitsown concepts and contribute to the world’santhropologicalheritage. Does the Egyptiananthropologicalcommunity have an outlook for overcoming the imitation stage of obtainingknowledgeIntoproducingtheoretical and empiricalknowledge, combine  Western scientific tradition, and privacy of the Egyptian society, which leads to produce a new knowledgealloy.? This general question necessarily leads us into a number of subsidiary questions: What are the development stages of Egyptiananthropology? Is the currentEgyptiananthropologyproduct as diversified as Egyptian social life? Is the Egyptiananthropologyabsorbed the new branches of science thataccompany the scientificdevelopment in the postmodern or liquidmodernity stage?